2021
DOI: 10.3390/jcm10184239
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Submaximal Exercise Followed by Short-Term Cold-Water Immersion on the Inflammatory State in Healthy Recreational Athletes: A Cross-Over Study

Abstract: Cold-water immersion (CWI) after exercise is a method used by sportsmen to improve recovery. The aim of the study was to assess the effect of a 3 min CWI on the inflammatory state by measuring levels of interleukin 6 (IL-6), interleukin 10 (IL-10), tumor necrosis factor α (TNF-α), and transforming growth factor β1 (TGF-β1), and activities of α1-antitrypsin (AAT) and lysosomal enzymes, including arylsulfatase (ASA), acid phosphatase (AcP), and cathepsin D (CTS D), in the blood of healthy recreational athletes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…This indicates that adaptive mechanisms occur in habitual winter swimmers [ 82 ]. In a study investigating the effects of a short-term immersion in cold water following a bout of exercise, IL-6 levels were found to be significantly higher compared to post-exercise rest at room temperature [ 83 ]. As increased levels of the cytokine IL-10 are known to be anti-inflammatory [ 84 ], it would be interesting to see whether this cytokine is increased during CWI.…”
Section: Resultsmentioning
confidence: 99%
“…This indicates that adaptive mechanisms occur in habitual winter swimmers [ 82 ]. In a study investigating the effects of a short-term immersion in cold water following a bout of exercise, IL-6 levels were found to be significantly higher compared to post-exercise rest at room temperature [ 83 ]. As increased levels of the cytokine IL-10 are known to be anti-inflammatory [ 84 ], it would be interesting to see whether this cytokine is increased during CWI.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, White et al [ 55 ] observed that CWI used after a high-intensity sprint run did not significantly reduce plasma concentrations of IL-6 and IL-8. Increased plasma levels of IL-6 may point to the sustained release of IL-6 from skeletal muscle in response to CWI-stimulated glycogenolysis [ 8 , 24 ]. The higher concentration of IL-6 after CWI-REST compared to the value AE in novices may result from modulation of muscle tissue as a consequence of exposure to cold.…”
Section: Discussionmentioning
confidence: 99%
“…In presented study, the concentration of IL-10 was statistically significantly higher after CWI-REST than after RT-REST in both studied groups. IL-10 is believed to be the primary anti-inflammatory agent, as it inhibits the production of pro-inflammatory cytokines by activated monocytes and macrophages [ 8 , 58 ]. The concentration of this cytokine in winter swimmers was significantly higher after CWI-REST than AE and BE.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations